2016
DOI: 10.1136/injuryprev-2015-041884
|View full text |Cite
|
Sign up to set email alerts
|

Preventing violence-related injuries in England and Wales: a panel study examining the impact of on-trade and off-trade alcohol prices

Abstract: ResultsReal on-trade (β=-0.661, p<0.01) and off-trade (β=-0.277, p<0.05) alcohol prices were negatively related with rates of violence-related ED attendance among the adult population of England and Wales, after accounting for the effects of regional poverty, income inequality, youth spending power and seasonal effects. It is estimated that over 6,000 fewer violence-related ED attendances per year in England and Wales would result from a 1% increase in both on-trade and off-trade alcohol prices above inflation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Neighborhood poverty and markers of economic stress, such as food insecurity, and financial dependence, have been linked to many forms of violence (Bonomi, Trabert, Anderson, Kernic, & Holt, 2014; Capaldi et al, 2012; Freisthler et al, 2006; Jewkes, Fulu, Roselli, & Garcia-Moreno, 2013; Johannesen & LoGiudice, 2013; Losel & Farrington, 2012; Luo, Florence, Quispe-Agnoli, Ouyang, & Crosby, 2011; Rehkopf & Buka, 2006; Slack et al, 2011). Previous ecological studies have linked national, regional, and state-level rates of poverty and economic stress to violence and other health outcomes (Holtgrave & Crosby, 2003; Page et al, 2016; Wolf, Gray, & Fazel, 2014), and research on indicators of financial hardship suggest that housing-related expenses contribute substantially to individuals' and families' financial stress (Bray, 2001; Kutty, 2005). As such, we measure economic stress using census data on residents’ median rent-to-income ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Neighborhood poverty and markers of economic stress, such as food insecurity, and financial dependence, have been linked to many forms of violence (Bonomi, Trabert, Anderson, Kernic, & Holt, 2014; Capaldi et al, 2012; Freisthler et al, 2006; Jewkes, Fulu, Roselli, & Garcia-Moreno, 2013; Johannesen & LoGiudice, 2013; Losel & Farrington, 2012; Luo, Florence, Quispe-Agnoli, Ouyang, & Crosby, 2011; Rehkopf & Buka, 2006; Slack et al, 2011). Previous ecological studies have linked national, regional, and state-level rates of poverty and economic stress to violence and other health outcomes (Holtgrave & Crosby, 2003; Page et al, 2016; Wolf, Gray, & Fazel, 2014), and research on indicators of financial hardship suggest that housing-related expenses contribute substantially to individuals' and families' financial stress (Bray, 2001; Kutty, 2005). As such, we measure economic stress using census data on residents’ median rent-to-income ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, evidence for the effectiveness of brief interventions in ED's have demonstrated a reduction in violence-related injury and consequences by targeting youth peer violence and alcohol misuse (Walton et al, 2010). Furthermore, there has been some evidence that increasing the price of alcohol has led to a reduction in violencerelated injuries requiring hospital treatment (Page et al, 2016). Increases in alcohol prices may be particularly beneficial to youth who represent a high-risk population for violence-related injuries treated in ED's.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to extend prevention programs for alcohol use to diminish the direct and indirect costs caused by alcohol-intoxicated patients. Public health programs and interventions are urgently required and may help to solve this problem [29].…”
Section: Predictors and Risk Factorsmentioning
confidence: 99%
“…Other preventive options may range from brief emergency room interventions to reduce re-admittance due to alcohol intoxications [30] to interventions at the national level by increasing taxes on alcoholic beverages [1], as a recent meta-analysis of the literature found that prices and taxes for alcoholic beverages are inversely related to the amount of alcohol consumption [4]. A disease modelling study suggested that violence-related ED visits might be reduced by 6000 a year in the UK by a 1% increase in the alcohol tax [29].…”
Section: Predictors and Risk Factorsmentioning
confidence: 99%